Cardiac disease in children with HIV-associated chronic lung disease at Queen Elizabeth Central Hospital, Blantyre, Malawi - Mapurisa, Gugulethu Newton (Kamuzu University of Health Sciences, 2022)
Over the past decade, more perinatally-infected children have survived despite previous assertions that few would reach adolescence. More complications of the chronic human immunodeficiency virus (HIV) are surfacing with improving survival. These include HIV, chronic lung disease (HCLD), and cardiac disease (1-5). Such complications were previously associated with delayed diagnosis and poor HIV control. However, there is growing evidence that prolonged disease by itself predisposes to cardiac disease (6,7). Cardiac disease in HCLD has not been researched in children stable on ART. The study aimed to describe the cardiac symptoms in HIV-infected children with chronic lung disease, who are stable on antiretroviral therapy (ART), and identify the prevalence of cardiac dysfunction. The study was conducted at Queen Elizabeth Central Hospital, QECH, a large teaching hospital in Blantyre, Malawi. It was a nested study in a prospective randomised controlled trial that corecruited consenting trial participants with HCLD who had been on ART for more than six months with virological suppression. Chronic lung disease was determined by spirometry of (FEV1 z-score < -1.0) with no reversibility (< 12%). Participant demographics were collected, and cardiac echocardiograms were done at baseline using a Sonosite M-turbo machine (8). Clinical data and demographic data were collected and analysed using STATA 14. Fourty-nine (49) of the 180 participants were recruited. The median age was 14.5 years; the interquartile range [IQR] was 8.4 – 19.8 years; 51.1% female. The mean CD4 cell counts were 640 ± 439 (87 – 2969). The mean Medical Research Council (MRC) dyspnea score was 2.3 ± v 1. Rheumatic heart disease was confirmed in 3 (6%) who were already on treatment at recruitment. 0 (0%) having pulmonary hypertension. In conclusion, our findings demonstrate low cardiac dysfunction and pulmonary hypertension levels in this cohort of HCLD in children. However, there is significant co-morbidity with acquired heart disease in this group set of children. Longer-term follow-up of these children is essential to identify if further cardiac dysfunction does not emerge in children on ART for a longer duration.